TINJAUAN YURIDIS PERLINDUNGAN KONSUMEN ATAS PERLINDUNGAN BERDASARKAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN DAN UNDANG-UNDANG BPOM - Ramadhan Sadam Husein; M Sifa Fauzi Yulianis (JOURNAL OF LAW AND NATION, 2024)
The purpose of this study is to discuss and analyze the form of consumer protection based on Law Number 8 of 1999 concerning Consumer Protection and discuss and analyze the form of consumer protection based on the BPOM Law. This research is included in normative juridical research. The results showed that the form of consumer protection based on Law Number 8 of 1999 concerning Consumer Protection consists of protection against the possibility of goods handed over to consumers not in accordance with what has been agreed with consumers and protection for consumers who get unfair conditions. The results of the study also show that there are many forms of consumer protection based on the BPOM Law, including socialization to the community, providing guidance to the community as business actors and consumers, direct inspection of food and beverage products in shopping center facilities from the BPOM team, supervision of direct coaching and inspection held by the BPOM team in food product circulation facilities.